Determining The Auspicious Day Of A Marriage Ceremony Using “Titen Science”: An ‘Urf Perspective In Andongsari, Jember - Tamam, Badrut; Krisnawati, Devi; Junaidi, Ahmad; Rato, Dominikus; Waeno, Mahammadaree (Hukum Islam, 2025)
This study aims to examine the tradition of determining the auspicious day before a marriage contract using titen science from the perspective of ‘urf in Andongsari Village, Ambulu Sub-district, Jember Regency. Ilmu titen, as part of Javanese customs, is a method based on custom and observation of past events (niteni), which is used to determine the right time for important events such as marriage. This research uses empirical legal method with legal sociology approach and conceptual approach. Data were obtained through interview, observation, and documentation techniques, with primary and secondary sources. The results show that although this tradition is highly upheld by the local community, the practice of determining a good day does not contradict the provisions of Islamic law. The pillars and conditions of marriage are still fulfilled, so this tradition can be seen as part of an effort to preserve Javanese cultural customs that are harmonious with Islamic teachings. The implications of this research show that the implementation of titen science not only helps maintain local wisdom, but also strengthens social and cultural harmony in the Andongsari Village community, which is predominantly Muslim.